Windows management instrumentation (WMI) security - Chew, Zhi Jie (2018)
Fileless attacks have been on a rise. A common similarity of all fileless attacks is that they use legitimate system software and one of it is called the Windows Management Instrumentation, also known as WMI. WMI based attacks are hard to track and well covert. There is no doubt that WMI based attack or even fileless attack will become more popular. Hence, there is a need to create a more sophisticated software to protect against WMI based attack.